The concept of the clutch control law of a car - Mykhalevych, M. H.; Fandieieva, A. Ye.; Михалевич, М. Г.; Фандєєва, А. Є. (Харківський національний автомобільно-дорожній університет, 2021)
Problem. The combination of comfortable automatic control of the car's transmission and at the same time preservation of high indicators of energy efficiency and cost of a design is possible by use of automatic mechanical transmission. The automatic clutch control system plays a significant role in providing comfort in such transmissions. The laws of controlling it are not perfect today. Goal. The aim of the work is to create a clear concept of the law of clutch control, which is easy to implement in a microcontroller and is well adapted to adapt to different driving conditions. Methodology. Graphically, the concept of the perspective law of clutch control is formed by two Bezier curves. One of the curves acts as a guide, and the other forms the surface of the law. Results. On the basis of the Bézier curves of the third degree the concept of the law is formed and the connection of the reference points of the Bézier curves with the physical parame-ters of the working process of vehicle movement is substantiated. Originality. The formation of the Bézier curve, which is decisive for the concept of the law, is formed on the basis of a typical working process of synchronization of the angular velocity of the clutch discs during the movement of the vehicle. In contrast to the laws of clutch control considered in the scientific litera-ture, the proposed concept provides for clutch control outside the site of the synchronization process and ensures the avoidance of jerks during further acceleration. Practical value. The proposed algorithm provides full engagement of the clutch only after full synchronization of the clutch discs. The formation of a special form of the law in the form of a curve tangent to the abscissa axis reduces the jerks when closing the clutch discs.
Концепція закону керування зчепленням
Keywords: clutch control law; Bezier curve; jerk effect; закон керування зчепленням; крива Безьє; ефект ривка; 629.3; 10.30977/AT.2219-8342.2021.48.0.17